Toxigenic Corynebacterium ulcerans isolated from a hunting dog and its diphtheria toxin antibody titer. (March 2016) - Katsukawa, Chihiro; Komiya, Takako; Umeda, Kaoru; Goto, Minami; Yanai, Tokuma; Takahashi, Motohide; Yamamoto, Akihiko; Iwaki, Masaaki
ABSTRACT: Toxigenic Corynebacterium ulcerans is a zoonotic pathogen that produces diphtheria toxin and causes a diphtheria‐like illness in humans. The organism is known to infect and circulate among dogs, which can then transmit it to humans. Furthermore, previous studies have found that C. ulcerans is carried by wild animals, including game animals. In the present study, we tested hunting and companion dogs for the presence of toxigenic C. ulcerans and succeeded in isolating the bacterium from a hunting dog. Moreover, several hunting dogs had serum diphtheria antitoxin titers that were higher than the titers required for protection in humans, suggesting a history of exposure to toxigenic Corynebacterium strains. Notably, ribotyping, pulsed‐field gel electrophoresis and tox gene sequencing demonstrated that the isolate from the hunting dog clustered with previously characterized C. ulcerans strains isolated from wild animals, as opposed to groups of isolates from humans and companion dogs. Interestingly, the wild animal cluster also contains an isolate from an outdoor breeding dog, which could have formed a bridge between isolates from wild animals and those from companion dogs. The results presented herein provide insight into the mechanism by which the zoonotic pathogen C. ulcerans circulates among wild animals, hunting and companion dogs, and humans.